The impact of upstream and downstream processing on the quality of oil bodies of partially de-hulled sunflower seeds - Mat Taher, Zarani (2016)
Few publications on oil bodies or oleosomes seem concerned about their quality (chemical and physical) ex-vivo. This work attempts to identify the main factors (processing and pre-processing) that affect the quality/integrity of sunflower seed oil bodies recovered through a wet-milling process. The physical state of seeds during wet milling had a significant impact on the quality of the oil body suspension. Pre-soaking for 6 hours before wet milling and multiple washing with alkaline buffer (0.1M sodium bicarbonate) was performed to isolate high quality oil body suspensions. It was evident from different physical measurements such as particle size, ζ-potential and light microscopy that pre-soaking had a positive influence on the quality of oil body suspensions with no significant signs of aggregation or coalescence. It was also observed that the resultant washed oil body suspensions were highly surface charged (-28.4 ± 1.2 mV) indicating very stable suspension phase behavior. Washing oil bodies not only removes non-integral, extraneous proteins (derived from the seed matrix) but enriches the lipid content including Tocopherol (α-tocopherol: 491.6 mg/kg of washed oil bodies compared with 252.6 mg/kg crude oil bodies). Changes in the composition of oil bodies after washing have been observed before, but this research also monitored the size of oil bodies after washing, and our results indicate that certain factors can shift the distribution of droplet size. It is believed that any change in average size of droplets indicate the presence of disrupted oil bodies whose surface chemistry has changed enough to compromise their integrity on washing. The retention of droplet size on washing may, therefore, be diagnostic for the recovery of intact oil bodies. An assessment of the integrity of oil bodies recovered from sunflower seeds after accelerated aging (5 months) was carried out. Free fatty acid was more pronounced in oil rather than oil bodies, this could be due to the elimination of some of the free acid bound to oil body during washing. Although some minor variation was observed during seed aging, however, the oil bodies remained stable in the final suspension. The results indicate that oil body membrane was extremely robust under extreme conditions and the integrity of oil bodies was preserved. In addition, oil bodies obtained in this study were resistant to oxidation due to the presence of naturally occurring antioxidants (including vitamin E) associated with them.. The results indicate that the physical barrier of surface membrane protein (oelosin) protect oil bodies against pro-oxidants.